FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN IKUTAN PASCA IMUNISASI COVID-19 - Hoirun Nisa; Putri Kurniawati; Rifka Qatrunnida; Dadang Mulyono (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Background: Evidence indicates that COVID-19 vaccines are effective at helping to prevent serious infection and risks of hospitalization due to COVID-19. Seven types of vaccines have been used in Indonesia. Adverse events following immunization (AEFI) may occur after the COVID-19 vaccination. Objective: This study aimed to determine factors associated with AEFI of the COVID-19 vaccination.Methods: This cross-sectional study included 160 respondents who had been vaccinated against COVID-19. Data were collected by using google form distributed through social media from October 12-20, 2021. Multivariate analysis was performed by using a logistic regression test.Result: The incidence of AEFI of the COVID-19 vaccination was 69.4%, and the AEFI symptoms were lower in the second dose of COVID-19 vaccine than the first dose. Poor dietary habits were associated with higher risks of the AEFI (OR=2.34 CI 95% 1.14-4.80). The second vaccine dose was related to decreased risks of the AEFI (OR=0.35 CI 95% 0.13-0.92).Conclusion: The incidence of AEFI of the COVID-19 vaccination was quite high, and the common AEFI was systemic symptoms. Dietary habits and vaccine doses were associated with the AEFI of the COVID-19 vaccination. These findings suggest that poor dietary habits may increase the risks of the AEFI, and decreased risks of the AEFI may be experienced in the second dose of COVID-19 vaccine. Further studies are warranted to explore the effects of both doses of COVID-19 vaccines on the AEFI.